تأثير استخدام وسيلة سيفركول فيديوسكرايب (Sparkol Videoscribe)في تعليم التراكيب لدى طلاب الفصل الخامس في المدرسة الابتدائية الإسلامية الحكومية بوكيت تنجي - Wati Mustika Rani; Yelfi Dewi; Arman Husni; Eka Rizal (Universitas Islam Negeri Sumatera Utara Medan, 2023)
In this study the researchers discussed tarkib learning, problem in tarkib learning is many of the students don't understand tarkib learning. Purpose of this research is (1) To find out the comparison of student tarkib learning using Video Scribe media with students using blackboard media. (2) To determine the effect of Sparkol Videoscribe learning media on fifth grade students of MIN Bukittinggi. As for the method used in this study is a quantitative method. The popolation consist of 93 students, researches took 62 students as a sample. The value of student tarkib learning is the average post-test for the exsperimental class is 84,83, while the average of the control class post-test is 77,67. The researcher found that the resultsof T count were 2,513 and T Table 2.000, so the result of T count were greater than T table. As For the result of the study,(1) there was an influence in tarkib learning between students who used Sparkol Videoscribe and students who used blackboard media, (2) and there is the infuence of Sparkol Videoscribbe learning media in tarkib class 5 Min bukittinggi.